Propuesta de mejoramiento mediante una adecuada planificación de la producción en el área de tejido de punto en la empresa textil “Fabrinorte CIA. Ltda.” en la ciudad de Otavalo. - Flores, Jorge J. (2022)
The titling work consists of proposing an improvement plan through adequate planning of production in the area of knitting in the textile company "FABRINORTE CIA. LTDA." For the development of the work, all the documentation referring to the company's knitting process was taken as information. Initially, the theoretical bases and regulations necessary for the development of the work were compiled, the same that will help us to better understand concepts that will be used in this degree work. In chapter two, the initial diagnosis of the company will be carried out, where historical information will be collected in order to also be able to tabulate important data of the company and, based on this analysis, to be able to develop the rest of the chapters. In chapter three, an adequate model will be developed for the planning of the knitted fabric production capacity and a correct management of unbleached fabric inventories, and with this information, in the following chapter, present a proposal for improvement in which it is intended that the production of circular fabric is more planned and controlled and in the same way have a better management in the inventories of raw material and product in process. In the last chapter, the proposal to improve the planning of knitted fabric production and an adequate management of inventories of product in process will be presented, as well as policies in the company for a better functioning of inventories will be defined. With the implementation of this titling work, it is wanted that the company in the area of knitting has greater control, both in the planning of knitting and in the warehouse of raw material and product in process and thanks to this to be able to have an adequate level of inventories, since the rest of the fabric processes start from this initial weaving process and with adequate control, orders and delivery can be better managed in a faster and more efficient way.